CHARACTER DESIGN BASE ON CARITA PANTUN SUNDA (Case Study: Carita Pantun Ronggeng Tujuh Kalasirna) - Gandara Permana (Balong International Journal of Design, 2020)
ABSTRACT In the era of globalization, communication and information technology have a very important role. On the other hand, one of the causes of the low interest of the community to preserve their cultural heritage is the low literacy of technology. Technological progress should be able to be used and utilized as one of the media for the preservation of the nation's cultural heritage. West Java, especially Sundanese people, has a variety of cultures and is currently entering an alarming phase, one of which is Carita Pantun. Carita Pantun is a performance art that has a function as a guide and a spectacle. This design will be focused on the design or design of characters that are packaged in 2D and 3D based on carita pantun West Java. The process to be carried out in this research is pre-production which includes the development of stories, visual design including concepts/ideas, characterization or study of characterizations, and visualization of characters or character designs, properties (assets), and settings (environment). The design target is aimed at adolescents aged 15-21 years. The results of this study will be used for further research on games and animation. Keyword: characterization, character design, carita pantun